2004
DOI: 10.1103/physrevb.69.054106
|View full text |Cite
|
Sign up to set email alerts
|

Orthorhombic distortion on Li intercalation in anatase

Abstract: The mechanism of the tetragonal-to-orthorhombic transformation upon Li-intercalation into anatase structured titania has been studied using first principle calculations. The primary mechanism for the formation of the orthorhombic phase is found to be the accommodation of donated charge in localized Ti-d yz orbitals leading to a cooperative Jahn-Teller-like distortion of the lattice. This model is examined further by considering electron addition states in pure anatase and the analogous structures of H 0.5 TiO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
99
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 30 publications
16
99
2
Order By: Relevance
“…These results provide no evidence that Li + migration is preferentially along the c axis, as in rutile, 42 or as suggested by Koudriachova et al for anatase. 58,59 The finding of a minimum energy octahedral site is consistent with experimental observations of Murphy et al 60 and Cava et al 61 who concluded, from neutron diffraction studies of the anatase to Li 0.5 TiO 2 phase transformation, that Li + ions reside on the octahedral sites, and this finding is broadly consistent with studies that identify two distinct sites for Li + occupation near the center of distorted oxygen octahedra. 62 A zigzag Li + migration path was also found by Lunell et al 63 using periodic Hartree-Fock calculations.…”
Section: Resultssupporting
confidence: 87%
“…These results provide no evidence that Li + migration is preferentially along the c axis, as in rutile, 42 or as suggested by Koudriachova et al for anatase. 58,59 The finding of a minimum energy octahedral site is consistent with experimental observations of Murphy et al 60 and Cava et al 61 who concluded, from neutron diffraction studies of the anatase to Li 0.5 TiO 2 phase transformation, that Li + ions reside on the octahedral sites, and this finding is broadly consistent with studies that identify two distinct sites for Li + occupation near the center of distorted oxygen octahedra. 62 A zigzag Li + migration path was also found by Lunell et al 63 using periodic Hartree-Fock calculations.…”
Section: Resultssupporting
confidence: 87%
“…This reaction is a good example of our method because the electrochemical characteristics of TiO 2 highly depend on their structural parameters such as crystallinity and polymorphs. [11][12][13][14] This phenomenon is well interpreted by general ab initio principles and Maxwell's equations without any empirical limiting factors; therefore, we expect that our method can be applied to general types of materials and reactions.…”
Section: Introductionmentioning
confidence: 99%
“…1͑a͔͒ shows no new features in the band gap, and the excess charge resulting from lithium intercalation occupies the bottom of the conduction band, as in previous calculations and in disagreement with the defect state observed in experimental XPS. 10,[50][51][52][53][54][55][56][57] The projected charge density associated with these occupied conduction band states is distributed over all the Ti atoms in the calculation; Fig. 2͑a͒.…”
Section: Resultsmentioning
confidence: 99%
“…[50][51][52][53][54][55][56][57] These studies report the excess electronic charge to be distributed over all the Ti atoms in the calculation, giving a metallic system with partial occupation of the bottom of the conduction band. These predictions of metallic behavior are incompatible with the localized defect state indicated by experimental photoabsorption 10 and disagree qualitatively with previous Hartree-Fock calculations.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation